Analisis Kebijakan Perubahan STAIN/IAIN Menjadi UIN - Hafizon, Ahmad; Rajab, Hairunnas (Institut Teknologi Pendidikan Indonesia, 2023)
The purpose of this writing is to find out the policy analysis of changing STAIN / IAIN to UIN. Theresearch method used is library research. The results of the study show the basic ideas andconcepts of developing IAIN towards UIN: 1) IAIN has not played an optimal role in the academicworld, bureaucracy, and Indonesian society as a whole. IAIN has more roles in society because itis in the context of da'wah, and 2) IAIN's curriculum has not been able to respond to science and technology developments and changes in society that are increasingly complex. background to the need for the conversion of IAIN to UIN: 1) changes in the type of Madrasah Aliyah education, and 3) there is a dichotomy between religious sciences and general sciences. 3) the change from IAIN to UIN is an opportunity for graduates to enter wider employment opportunities, 4) the change from IAIN to UIN is in the context of providing opportunities for IAIN graduates to carry out vertical mobility, and 5) the change from IAIN to UIN is also a demand for the implementation Professional education, high quality and offers many choices.